Recent and future variability of the ice-sheet catchment of Sermeq Kujalleq (Jakobshavn Isbræ), Greenland - Anja Løkkegaard; William Colgan; Andy Aschwanden; Shfaqat Abbas Khan (Journal of Glaciology)
Knowledge of ice-sheet catchments is critical for mass-balance assessments, especially glacier-scale input–output budgets. This study explores variations in the catchment of Sermeq Kujalleq, or Jakobshavn Isbrø, Greenland. Six observation-based catchment delineations are evaluated along with a 16-member catchment ensemble calculated from ice-sheet models within the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). The ‘present-day’ ISMIP6 ensemble mean area was found to be $\sim 6.3\%$ larger than the mean of the observed catchments. Ensemble spreads were comparable in size, $\pm 12.3\%$ and $\pm 15.4\%$, suggesting models are able to delineate the present-day catchment with the same degree of uncertainty as observational methods. The mean catchment area of a 13-member ISMIP6 ensemble shows temporal variation, increasing $\sim [ 2.7,\; \, 5.7,\; \, 9.1] \%$ under three ocean forcing scenarios and a RCP8.5 projection based on one GCM from 2015 to 2100, primarily as the southern catchment boundary migrates southward. This is interpreted as Sermeq Kujalleq exhibiting dynamic piracy, re-directing ice away from adjacent land terminating glaciers. For mass-balance assessments, present-day catchment delineation is more important than capturing the temporal evolution of individual catchments. However, the modeled temporal changes in catchment area are potentially underestimated, as the models exhibit insufficient acceleration of inland ice flow.